Lagrangian Floats for Deep Convection - D'Asaro, Eric A (1998)
I aim to understand the process of deep convection in the ocean. Near surface water is mixed to great depth at a few high latitude locations, thereby forming the deep and bottom masses of the ocean. This proposal has supported the development and deployment of neutrally buoyant floats in the Labrador Sea in the winters of 1997 and 1998 and the analysis of the resulting data. These floats provide detailed information on the processes and rates of deep convection. See also ADM002252.